The role of complement in the treatment of invalid procedure - Jassim Mohammed , Assist.Lect. Ali; Sadeq Saget, Assist.Lect. Sarah (Basra studies journal, 2022)
Correcting the invalid procedure by complementing it is one of the most important means used in correcting procedural nullity, as it is granted by granting the trial court the authority to assess the correction of the error by the litigants, at their request, and in light of what the law determines or the court decides, extended periods that must be taken into account by the litigants. To provide what addresses the wrong procedure or complete the missing procedures, we explain this through a statement of the position of the Iraqi and Egyptian civil pleadings, while clarifying the role of the Iraqi judiciary in how to deal with these defective procedures, and how to address them in light of the lack of explicit provisions in the Civil Procedure Code No. 83 for the year 1969.